2018
DOI: 10.21248/zaspil.61.2018.486
|View full text |Cite
|
Sign up to set email alerts
|

Degrees as nominalized properties: evidence from differential verbal comparatives in Mandarin Chinese

Abstract: Whether degrees should be modeled as simple semantic primitives or ontologicallycomplex entities has been an issue in recent formal semantic research. This article aims tomake a contribution to this scholarly enterprise by investigating the Differential VerbalComparative (DVC) construction in Chinese. DVCs exhibit peculiar properties : (i)obligatory differentials, and (ii) DPs as differentials(e.g., liang ben xiaoshuo ‘two CL novel’).We propose that a degree is the entity correlate of a property that is formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As we stated in the beginning of this paper, there are two core questions behind this phenomenon: (i) whether a case of apparent surface variability in making comparison reflects variability in grammar, and (ii) which component of grammar (if any) can a case of variability in comparison be reduced to (cf. Kennedy 2009;Luo & Xie 2018). Various proposals have been put forth, e.g., the degree abstraction parameter (Beck et al 2004;Beck et al 2009) We have shown that there may exist different strategies in making comparison of equality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we stated in the beginning of this paper, there are two core questions behind this phenomenon: (i) whether a case of apparent surface variability in making comparison reflects variability in grammar, and (ii) which component of grammar (if any) can a case of variability in comparison be reduced to (cf. Kennedy 2009;Luo & Xie 2018). Various proposals have been put forth, e.g., the degree abstraction parameter (Beck et al 2004;Beck et al 2009) We have shown that there may exist different strategies in making comparison of equality.…”
Section: Discussionmentioning
confidence: 99%
“…There are two driving questions behind this line of research: (i) whether a case of apparent surface variability in making comparison reflects variability in grammar, and (ii) which component of grammar (if any) can a case of variability in comparison be reduced to (cf. Luo & Xie 2018). Answers to the questions vary as different scholars entertain different proposals (see Beck (2012) and Hohaus & Bochnak (2020) for a detailed overview).…”
Section: Introductionmentioning
confidence: 99%
“…Li's mapping-based analysis of the DVC is largely motivated by the observation that when the differential phrase in the DVC is not a measure phrase (MP), it shares properties with DP objects that purport to denote individuals. Luo & Xie (2018) take issue with this treatment, and show there are empirical observations that set non-MP differential phrases in DVC sentences apart from genuine DPs. For instance, when the differential phrase in a DVC sentence is a numeral + classifier phrase, it can be preceded by the degree-modifying "na(me)", a modifier that cannot precede a genuine DP ( 49).…”
Section: Differential Verbal Comparatives In Mandarin Chinese and The...mentioning
confidence: 99%
“…In short, Luo & Xie's (2018) approach to the problem raised by DVCs under an enriched definition of degrees: degrees as kinds.…”
Section: Differential Verbal Comparatives In Mandarin Chinese and The...mentioning
confidence: 99%